Ichthyosis (concept, pathohistology, clinical picture, treatment) - Tatyana Gennadyevna Takhtarova; Zarema Rimovna Khismatullina; Lyudmila Dmitrievna Panova; Anastasia Nikolaevna Panova (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Ichthyosis is a skin disease that is hereditary, has pronounced symptoms in the form of a violation of the skin, and the presence of formations resembling fish scales. It is possible to distinguish different approaches to the definition of ichthyosis, based on the modern study of this issue. Ichthyosis is classified by type: congenital and acquired. Congenital ichthyosis has its own classification depending on the manifestation of changes in the skin, the course of the disease, concomitant pathologies. Congenital ichthyosis is divided into ordinary (vulgar autosomal dominant, simple) ichthyosis, lamellar ichthyosis (dry ichthyosiform erythroderma, "collodion child", lamellar ichthyosis), X-linked ichthyosis (ichthyosis associated with the X chromosome, blackening ichthyosis), congenital bullous ichthyosiform erythroderma (erythroderma Broca's disease, ichthyosiform epidermolytic hyperkeratosis), fetal ichthyosis (intrauterine ichthyosis, universal hyperkeratosis, "Harlequin fetus", congenital keratosis), other congenital ichthyosis. Ichthyosiform conditions (the so-called acquired ichthyosis) are divided into symptomatic, age-related (senile), discoid ichthyosis. The causes of acquired ichthyosis can be various diseases, taking medications, improper skin care, unbalanced nutrition. Each form of ichthyosis differs by the type of inheritance, prevalence in the population, clinical picture, verified by histological examination of skin biopsies and electron microscopic examination of the skin. It may be accompanied by seasonality of exacerbation of the clinical picture, association with other diseases (allergic, diseases of the gastrointestinal tract, congenital malformations). There is no specific treatment for ichthyosis. In systemic therapy, derivatives of vitamin A are used, keratolytics, as well as moisturizing and emollient agents are used for external treatment. The use of therapeutic baths, general ultraviolet irradiation is effective.